(a) $\delta H = T\delta S + V\delta P$

(b) $\delta H = S\delta T + V\delta P$

(c) $\delta H = -S\delta T + V\delta P$

(d) $\delta H = \delta E + P\delta V$

Answer: $\delta H = T\delta S + V\delta P$

Given, $H = E + PV$

Differentiating both sides we get,

$\delta H = \delta E + P\delta V + V \delta P$

$\Rightarrow \delta H = T\delta S - P \delta V + P\delta V + V\delta P$

$\therefore \delta H = T\delta S + V \delta P$ $[\because \delta E = T\delta S - P\delta V]$

Ask Question

Tag:MathPhyChemBioOther

Take Test

...